Systematics of the east Palaearctic pear psyllids (Hemiptera: Psylloidea) with particular focus on the Japanese and Korean fauna - Cho, Geonho; Burckhardt, Daniel; Inoue, Hiromitsu; Luo, Xinyu; Lee, Seunghwan (Zootaxa, 2017)
The confused taxonomy of the east Palaearctic pear psyllids, serious pests on cultivated pear, is reviewed. Fifty-six nominal species have been reported from Pyrus, 25 of which we consider valid and ten as not being associated with Pyrus. Our taxonomic revision suggests that, in Korea, four Cacopsylla species develop on pear: the univoltine C. burckhardti Luo et al. previously misidentified as C. pyrisuga (Foerster), the polyvoltine, seasonally dimorphic C. jukyungi (Kwon) (winter form ‘cinereosignata’ Luo et al., summer form ‘jukyungi’), commonly found in Korean pear orchards, and C. maculatili Li (winter form ‘maculatili’, summer form ‘qiuzili’ Li) previously misidentified as C. pyricola (Foerster) by some authors, as well as the probably polyvoltine but not dimorphic C. sandolbaea (Park & Lee). The former three species (C. burckhardti, C. jukyungi, misidentified as C. chinensis (Yang & Li), and C. maculatili) occur also in Japan. Keys to the adult and fifth instar immatures as well as short biological notes are provided, and C. jukyungi and C. sandolbaea are redescribed. Following nomenclatorial changes are proposed: Cacopsylla betulaefoliae (Yang & Li, 1981) = Psylla heterobetulaefoliae Yang & Li, 1981, syn. nov.; Cacopsylla bidens (Šulc, 1907) = Psylla jiangli Yang & Li, 1981, syn. nov.; Cacopsylla jukyungi (Kwon) = C. cinereosignata Luo et al., syn. nov.; Cacopsylla maculatili Li = C. qiuzili Li, syn. nov.; Cacopsylla nigella (Konovalova), comb. nov. from Psylla. The synonymy of P. obongsana Kwon with C. sandolbaea is confirmed.